UCAI 2022 - 3rd International Workshop on User-Centered Artificial Intelligence - Buschek, Daniel; Hauptmann, Hanna; Heuer, Hendrik; Loepp, Benedikt; Riener, Andreas; Yigitbas, Enes (Proceedings of the Mensch Und Computer 2022 (MuC ’22))

Design and Evaluation of a Collaborative UML Modeling Environment in Virtual Reality - Yigitbas, Enes; Gorissen, Simon; Weidmann, Nils; Engels, Gregor (International Journal on Software and Systems Modeling (SoSyM))

Einsatz und Evaluation von Virtual Reality-Technologie in einem Informatik-Seminar - Yigitbas, Enes

Model-driven Design and Management of Professional Education Programmes - Wolters, Dennis; Engels, Gregor (ICSOB'22 Companion Proceedings)

A Scalable and Extensible Architecture for a Crowd-Based Prototype Validation Platform - N., N.

Conception and Implementation of a Situation-specific Design Thinking Tool - N., N.

Design and Evaluation of AR-Assisted End-User Robot Path Planning Strategies - Krings, Sarah Claudia; Yigitbas, Enes; Biermeier, Kai; Engels, Gregor (Proceedings of the 14th ACM SIGCHI Symposium on Engineering Interactive Computing Systems (EICS 2022))

Extending Business Model Development Tools with Consolidated Expert Knowledge - Gottschalk, Sebastian; Kirchhoff, Jonas; Engels, Gregor (Business Modeling and Software Design)

eMoflon: : Neo - Consistency and Model Management with Graph Databases - Weidmann, Nils; Anjorin, Anthony (STAF 2021 Workshop Proceedings: 9th International Workshop on Bidirectional Transformations, Joint Workshop on Foundations and Practice of Visual Modeling and Data for Model-Driven Engineering, International workshop on MDE for Smart IoT Systems, 4th International Workshop on (Meta)Modeling for Healthcare Systems, and 20th International Workshop on OCL and Textual Modeling co-located with Software Technologies: Applications and Foundations, Federation of Conferences {(STAF} 2021), Virtual Event / Bergen, Norway, June 21-25, 2021)

Von datenbasierter zu datengetriebener Geschäftsmodellentwicklung: Ein Überblick über Software-Tools und deren Datennutzung - Gottschalk, Sebastian; Yigitbas, Enes
Die kontinuierliche Weiterentwicklung des eigenen Geschäftsmodells ist für eine Organisation von entscheidender Bedeutung, um wettbewerbsfähig und somit nachhaltig erfolgreich zu bleiben. Während für die Entwicklung neuer Geschäftsmodelle häufig Workshops und einfache Software-Tools zur Visualisierung genutzt werden, wurden in der Forschung bereits erste Ansätze von datengetriebener Geschäftsmodellentwicklung (GME) vorgestellt. Diese Ansätze nutzen dabei Daten, Informationen oder auch Wissen aus internen und externen Unternehmensquellen, um den GME-Prozess zu unterstützen. Innerhalb dieses Beitrags zeigen wir einige Ansätze aus der aktuellen Literatur und analysieren wie ihre Datennutzung den GME-Prozess unterstützt. Weiterhin stellen wir mit dem BMDL Feature Modeler ein Tool vor, welches den GME-Prozess mit Expertenwissen unterstützt.